Simultaneous separation of killed Pasteurella multocida cells and removal of formalin using tangential flow membrane filtration for production of toxoid vaccines - Kapri, Mohammad Rizal; Lajis, Ahmad Firdaus; Mohamad, Mazlan; Halim, Murni; Mohd Yusoff, Md Sabri; Ariff, Arbakariya (Knowledge Transfer Programme – Ministry of Higher Education, Malaysia, 2015)
Formalin is used to inactivate bacterial products for the production of vaccines that use and inactive bacterial toxin to produce immunity, which is commonly known as toxoid vaccines. Formalin is highly toxic to human and animals, regardless of method intake. The commercial production of killed bacterial vaccines based on Pasteurella multocida for veterinary use is mainly depends on the effective separation of the killed bacterial cell and separation of formalin from large volumes of fermentation broth. Batch centrifugation followed by washing with buffers is applicable for laboratory scale but not for large scale industrial process. In this project, tangential flow filtration (TFF) or cross flow membrane filtration system was used as rapid drive in the separation of killed bacterial cells of P. multocida and simultaneously to remove formalin from the cell suspension. The fermentation broth containing P. multocida was prepared using stirred tank bioreactor and the bacterium was killed with 3% (V/V) formalin. The separation of killed cells and the removal of formalin were simultaneously performed using TFF with microporous membrane (0.22 and 0.45 μm) operated continuously for several cycles with various modes. The operational variable of the TFF system such as average trans-membrane pressure, cross flow rate and flux were also investigated. Under the best conditions, formalin in concentrated cell suspension was successfully reduced to lower than 0.03% (v/v). The permitted formalin concentration in vaccine product, as suggested by British Pharmacopeia, shall be not exceeded 0.5 g/L. This indicates that TFF system is promising to produce industrial killed bacterial vaccines that comply with good manufacturing practice (GMP) guidelines.